Penguatan Ekonomi Santri melalui MUSCOOP (Mambaul Ulum Syariah Cooperative) Tiris Probolinggo - Arifin, Misbahul; Qomariyah, Qomariyah (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study focuses on strengthening the economic empowerment of santri through the role of MUSCOOP (Mambaul Ulum Syariah Cooperative) at Pondok Pesantren Mambaul Ulum Al-Murtadlo, Tiris Probolinggo, as a model of Islamic entrepreneurship transformation that integrates Sharia values with productive economic practices. The purpose of this research is to analyze the contribution of the Syariah cooperative in shaping santri’s economic independence and to identify the socio-economic impacts emerging within the pesantren environment. This study employed a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation study. The research was conducted at Pondok Pesantren Mambaul Ulum Al-Murtadlo, Tiris, Probolinggo, from August 20 to 25, 2025. The findings reveal that MUSCOOP not only functions as a Sharia-based economic institution but also as an effective medium for entrepreneurship education. Santri gained practical experience in business management, financial literacy, and Islamic business ethics, which in turn enhanced their independence, skills, and mindset regarding the importance of Islamic value-based economic self-reliance. The implications of this study emphasize that Sharia cooperatives in pesantren can serve as a strategic solution for community economic empowerment, while at the same time offering a new perspective for the development of Islamic entrepreneurship rooted in traditional educational institutions.